The problem of effectiveness of a procedural act performed “prematurely” – a few comments in relation to the decision by the European Court of Human Rights on 13 december 2018, 21497/14 (Witkowski) - Woźniewski, Krzysztof (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Provisions of procedural criminal law, awarding participants of criminal proceedings with the right to perform specific procedural acts in order to elicit related procedural effects, often simultaneously specify a deadline for performing such acts. A failure to meet such a deadline as a rule leads to a negative consequence, i.e. ineffectiveness of the procedural act carried out in violation of the said deadline. The problem also occurs when making a procedural action prematurely. The article will be devoted to these issues.

Przepisy prawa karnego procesowego, przyznając poszczególnym uczestnikom postępowania karnego uprawnienia do dokonywania określonych czynności procesowych w celu wywołania związanych z nimi skutków procesowych, często jednocześnie określają termin dla ich dokonania. Niedotrzymanie tego terminu zazwyczaj pociąga za sobą negatywną konsekwencję procesową w postaci bezskuteczności czynności procesowej dokonanej z naruszeniem terminu do jej dokonania. Problem występuje także przy dokonaniu czynności procesowej przedwcześnie. Tym właśnie zagadnieniom poświęcony został artykuł.
Keywords: effectiveness of procedural action; judgment; premature; skuteczność czynności procesowej; wyrok; przedwcześnie